AB1003 DELAY IN DIAGNOSIS OF KAWASAKI DISEASE IS THE COMMONEST PROXIMATE REASON FOR DEVELOPMENT OF GIANT CORONARY ARTERY ANEURYSMS- OUR EXPERIENCE AT CHANDIGARH, NORTH INDIA. (June 2019) - RAKESH, KUMAR; Jindal, Ankur; Gupta, Anju; Suri, Deepti; Singhal, Manphool; Singh, Surjit
Abstract : Background: Long-term effects of Kawasaki disease (KD) depend primarily on development of coronary artery abnormalities. Giant coronary aneurysm (GCA) is the one of the most severe sequelae in KD. Regression of giant aneurysm is rare. Data from Indian subcontinent is limited. Herein, we review patients with KD who had GCA. Objectives: To describe the profile of patients with KD who developed GCA from a cohort of KD patients at Advanced Pediatric Centre, Postgraduate Institute of Medical Education and Research (PGIMER), Chandigarh. Methods: Records of all children diagnosed to have KD during 1994-2017 were analysed. Out of the 680 patients with KD, clinical details of 17 (2.5%) children with GCA were retrieved. Results: Diagnosis of GCA was based on coronary artery diameter ≥8 mm or ≥+10 z score. Six of 17 children (boys 13; girls 4) with GCA had incomplete KD. Diagnosis of KD was made at a mean of 17.2±12.2 days of fever. Eight (47%) children were <1 year. Median age of diagnosis was 18 months (range 1.5 months-12 years). Left anterior descending (LAD) coronary artery was affected in 82% followed by right coronary artery (RCA) in 59%. Multiple GCA >1) were seen in 65% patients. All patients had received first line therapy as IVIg. Median day of IVIg administration was 15.5 days. Twelve had received additional therapy with infliximab. Thromboses developed in 4 (23.5%) and most common coronary affected was LAD. All patients were started on anticoagulation therapy and there were no significant complications related to anticoagulation. Conclusion: Results of this study suggest that GCA develop more commonly in infants and young children. Delay in diagnosis and consequent administration of IVIg appears to be the commonest proximate cause of development of GCA. References: [1] Fukazawa R, Kobayashi T, Mikami M, et al. Nationwide Survey of Patients With Giant Coronary Aneurysm Secondary to Kawasaki Disease 1999-2010 in Japan. Circ J. 2017;25;82(1):239-246 [2] Gupta A, Singh S, Rohit M, et al. Giant coronary aneurysms in Kawasaki Disease. Indian J Pediatr. 2014;81(4):401-2. [3] Tsuda E, Hamaoka K, et al. A survey of the 3-decade outcome for patients with giant aneurysms caused by Kawasaki disease. Am Heart J. 2014;167(2):249-58. Disclosure of Interests: None declared